Bikol Dictionary - Mintz, Malcolm W. (University of Hawai'i Press, 2018)
The Bikol language of the Philippines, spoken in the southernmost peninsula of Luzon Island and extending into the island provinces of Catanduanes and Masbate, is presented in this bilingual dictionary. An introduction explains the Bikol alphabet, orthographic representation (including policies adopted in writing Spanish and English loan words), foreign sounds in Bikol, and Bikol phonology. A section on the use of the dictionary outlines these elements: affixes, tenses, verbal and nonverbal stress, combined affix forms, the causative series "pa-,""mang-" and "pang-" series, "pang-" as a nominal, "maki-" and "paki-" series, "hing-" series, unintentional action, ability series, "magin," and plural nouns, verbs, and adjectives. The Bikol-English and English-Bikol dictionary sections follow.